Electroluminescence of self-assembled InAs quantum dots in p-i-n diodes - Malzer, Stefan; et al. (physica status solidi (b), 2001)
Carrier injection and subsequent radiative recombination in InAs/GaAs self-assembled quantum dots (SADs) is investigated by means of a double-hetero (DH) p-i-n structure, where a SAD laver is embedded at the center of the narrow intrinsic GaAs region. Low temperature electroluminescence shows clearly the filling of electronic states of the dots with increasing voltage. Relating the experimental data to the calculated band structure, the onset of excited SAD-level luminescence is closely related to the occupation of the excited hole levels, whereas the electron levels seem to be filled to a higher degree throughout the investigated voltage regime.